2023
DOI: 10.1021/acsmaterialslett.2c01046
|View full text |Cite
|
Sign up to set email alerts
|

A Deeper Understanding of H2 Evolution Entirely from Water via Diborane Hydrolysis

Abstract: Hydrogen (H2) has drawn extensive attention due to its superior gravimetric capacity density and eco-friendly nature. Nowadays, hydrogen is mainly produced by the steam reforming of natural gas, a process that leads to massive emissions of greenhouse gases. Very recently, H2 evolution upon hydrolysis of diboranes (e.g., B2(OH)4 and B2pin2) is promising because both H atoms of the released H2 are obtained from water. This is different from the hydrolysis of sodium borohydride, dimethylaminoborane, ammonia boran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 211 publications
(235 reference statements)
0
9
0
Order By: Relevance
“…This is a complete departure from the principles of the utilization of hydrogen energy. [22] Additionally, the large-scale industrial application of hydrogen is severely hampered by its safety issues as to storing and transportation, because of its extremely low density, super-high explosibility, and liquefaction Scheme 1. The synthesis of Pt/CNT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a complete departure from the principles of the utilization of hydrogen energy. [22] Additionally, the large-scale industrial application of hydrogen is severely hampered by its safety issues as to storing and transportation, because of its extremely low density, super-high explosibility, and liquefaction Scheme 1. The synthesis of Pt/CNT.…”
Section: Introductionmentioning
confidence: 99%
“…This is a complete departure from the principles of the utilization of hydrogen energy. [ 22 ] Additionally, the large‐scale industrial application of hydrogen is severely hampered by its safety issues as to storing and transportation, because of its extremely low density, super‐high explosibility, and liquefaction dilemma. [ 23 ] Therefore, it still remains a severe challenge to develop hydrogen storage materials, including HCOOH, [ 24 , 25 , 26 , 27 ] hydrazine, [ 28 ] borohydrides [ 29 , 30 ] and alcohols, [ 31 ] for avoiding high cost and the safety risks in the production, storage, and transportation of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrahydroxydiboron [B 2 (OH) 4 ] has been gaining significant attention as a versatile reducing agent in organic synthesis. [5][6][7][8][9][10][11] Recently, we and other research groups have reported that B 2 (OH) 4 reduces various functional groups such as alkenes, alkynes, [7] heteroarenes, [7b,8] aryl halides, [7c] aryl ketones, [9] and nitroarenes [7d,8,10] in the presence of transition-metal catalysts. It has also been reported that the B 2 (OH) 4 -promoted reductions often proceed through transition-metal-catalyzed transfer hydrogenation from water under aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the B 2 (OH) 4 -promoted reductions often proceed through transition-metal-catalyzed transfer hydrogenation from water under aqueous conditions. [6] These findings prompted us to develop a catalytic debenzylation of Oand N-benzyl groups by B 2 (OH) 4 -mediated water-based transfer hydrogenolysis.…”
Section: Introductionmentioning
confidence: 99%